Novel Potential Immune Response Biomarkers to Multidrug-Resistant Tuberculosis in the Last Five Years - Unicha, Mutiara Shinta Noviar; Wayan Tunas Artama; Niken Irfa Nastiti (Institute of Topical Disease Universitas Airlangga, 2022)
Rapid and accurate detection performs an important role in the control of raising MDR-TB. Currently, studies on biomarkers as targets for TB diagnostic tests using immune response products to indicate the presence, mycobacterial load, early markers, and activity, diï¬€ erentiation, and progression markers of TB infection are rapidly available. This systematic review aims to summarize the last ï¬ ve years of potential biomarkers studies from the immune response for MDR-TB rapid diagnostic development. The authors performed a literature search on four databases as ProQuest, EBSCO Academic Search, Universitas Gadjah Mada Online Library Journal Database, and Google Scholar, retrieved from January 2016 to December 2021. In total, 18,288 articles were identiï¬ ed and three tudies met the inclusion criteria. Several promising biomarkers were found for MDR-TB diagnosis purposes, such as sCD14, PGLYRP2, FGA, Indoleamine 2, 3- dioxygenase (IDO), and Complement Receptor 2 (CR2). A combination of sCD14, PGLYRP2, and FGA were bringing a diagnostic design with a higher sensitivity (94.7%) and speciï¬ city (80%) than the design of a single protein. Higher IDO activity towards the MDR-TB group than in the DS-TB group with a sensitivity of 87.50 %, speciï¬ city of 72.22 %. CR2 was the main focus due to its association with IL-6. After induction of CR2 peptide in a dose-dependent manner, the expression level of IL-6 was decreased signiï¬ cantly. It might because of CR2 peptide regulating the macrophages proinï¬‚ ammatory cytokines secretion to decrease the local inï¬‚ ammation of the immune response. These biomarkers are strong candidates for MDR-TB diagnosis due to their important role as the pathogenesis marker of MDR-TB. There is a need of further research to investigate those immune response products and their role to eliminate infection of Mycobacterium tuberculosis directly.